2016
DOI: 10.1159/000444735
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Soy Foods on the Development of Breast Cancer and the Prognosis of Breast Cancer Patients

Abstract: The relationship between soy food intake and breast cancer has been rigorously investigated for more than 25 years. The identification of isoflavones as possible chemopreventive agents helped fuel this line of investigation. These diphenolic compounds, which are found in uniquely-rich amounts in soy beans, possess both estrogen-dependent and -independent properties that potentially inhibit the development of breast cancer. Observational studies show that among Asian women higher soy consumption is associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 78 publications
(98 reference statements)
0
35
0
5
Order By: Relevance
“…Tofu is a versatile ingredient with many health benefits. As a particular soy food, It also contains high concentration of isoflavones, which possess both estrogen-dependent and -independent properties that potentially inhibit the development of breast cancer [49]. It has been hypothesized that isoflavones protect against breast cancer through competitive binding to estrogen receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Tofu is a versatile ingredient with many health benefits. As a particular soy food, It also contains high concentration of isoflavones, which possess both estrogen-dependent and -independent properties that potentially inhibit the development of breast cancer [49]. It has been hypothesized that isoflavones protect against breast cancer through competitive binding to estrogen receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to gluten‐free foods, soy products are generally regarded as healthy. Although soy contains protease inhibitors, saponins and phytates, their high isoflavone and phytoestrogen content, as well as dietary fibers, lipids, and peptides contribute to positive health effects (Messina, ).…”
Section: Fumonisins In Foodstuffs and Agricultural Commoditiesmentioning
confidence: 99%
“…Clinical trials consistently showed that isoflavone consumption does not adversely affect the markers of breast cancer risk. Furthermore, soy intake after breast cancer diagnosis significantly reduced the cancer recurrence and improved the overall survival [161].…”
Section: Soy Isoflavones and Cancermentioning
confidence: 99%